Goðakirkja - the Icelandic Church During the Commonwealth Era - Gogłoza, Włodzimierz (Prawo Kanoniczne, 2020)
Goðakirkja (the chieftains church) is the name given by the modern Icelandic historians to the early Catholic Church of Iceland. The name signifies the unusually large amount of control which the prominent members of the laity used to have over the Icelandic church and its properties. All the churches in Iceland except the one built next to the General Assembly (Alþingi) were privately owned and managed. Most of the tithe was collected by laymen. The secular elites took part in electing the local bishops, and all the commands of the foreign archbishops were treated as “new laws” (nýmæli), temporary resolutions which were to be in force only for three years, after which they were to be considered anew by the members of the Law Council (Lögrétta). The aim of present article is to retrace the early development of the institutional Church in medieval Iceland. Special consideration is given to the conversion of Icelanders, the functions of the early church buildings, the differences between various classes of priest, and the unusual nature of the tithe collected in Iceland. Finally, I outline the so called staðamál that is the conflict over the control of the privately built churches.